Edaphic forms of phosphorus in no-tillage cropping sequences in the Argentine southern central Pampas - Suñer, Liliana (2018)
Agriculture significantly affects phosphorus (P) availability, thereby modifying P equilibrium. The objective of this study was to evaluate the effect of different crop sequences on the dynamics of soil P forms under no tillage. Soil samples were collected from a system of five sequences initiated in 1998. The agricultural sequences followed the scheme crop diversity (CD), crop-pasture (CP, without grasses), traditional crops 1 (TC1, for limited soils), traditional crops 2 (TC2), and traditional crops 3. TC3). The available P (Pe) was determined and soil P was fractionated. Organic P extracted with NaOH (PoNa) was analyzed by spectrometry UV–visible and IR. Under CP, the available P decreased in both organic and inorganic labile forms, whereas PoNa values increased. Higher Pe was observed in TC1and TC3. The E4/E6 rates showed that the systems with the lowest degree of aromaticity were CP, TC1 and TC3. These three management sequences presented high PoNa values and, from these values, CP showed lower values for Pe, indicating differences in the chemical quality of the molecule. The 1050/1260 spectra, which relates an aliphatic ester to an aromatic ester, indicated that the CP and TC3 ratios were 1.3 and 0.94, respectively. In other words, the predominant type of ester in CP is aliphatic and in TC3 predominant esters would be of the aromatic type. Crop rotations can produce changes in organic P forms, which will modify the predominant functional group and the way this nutrient interacts with the soil matrix. Inclusion of pastures in a rotation maintains plant-available P at lower levels. However, this is the sequence that keeps moderately labile P (PoNa) at higher levels.